Effect of an intervention programme based on the verb as a unit of semantic-executive synthesis on a child with ADHD - Pelayo Gonzalez, Héctor Juan; Duran Hernandez, Diana Isabel; Mendez Balbuena, Ignacio; Lopez Cortes, Vicente Arturo; Reyes-Meza, Veronica (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Attention Deficit Disorder is highly prevalent among the child population and its symptoms hinder development in school, family, and social aspects. It is known that these children may present important difficulties in language development, specifically in the regulation, development of meanings, shaping, and stability of internal images, and problems in the evocation of information. If intervention programs were to include these aspects of language as a means of treatment, care would improve. In this paper, we evaluated, through a case study, whether using verbs can integrate semantic and executive aspects that will enhance regulatory and attentional processes in a child with ADHD and present a program based on verbs as the unit of semantic-executive synthesis used. The results indicate a significant decrease in errors in the neuropsychological factors of motor organization, audio-verbal retention, visual retention, phonemic, and global spatial integration. It is necessary that intervention programs are consistent from the point of view of the brain-behavior relationship and that the selection of tasks includes the semantic and executive aspects of language to achieve the recovery or development processes.